‘[A]nd when I came to her I found she was not a virgin’: A contextual re-reading of Deuteronomy 22:13–21 among Nigerian Christians - Ademiluka, Solomon Olusola (Verbum et ecclesia, 2023)
The traditional African society attached special value to female virginity, associating it with personal purity and honour. But today in Nigeria, virginity has lost its importance to premarital sex. The neglect of this virtue should be a concern to the Church in Nigeria because this is now a rising trend being witnessed among the Christian youth. This article, therefore, attempted a re-reading of Deuteronomy 22:13-21 as a response to the problem of premarital sex among Nigerian Christian youth. It employed the historical-critical exegesis and the descriptive approach. The work revealed that several factors are responsible for the prevalence of premarital sex in Nigeria, including a lack of sex education from parents, and the influence of western culture, among others. It also discovered that premarital sexual behaviour has social implications, particularly for female youth. These include unwanted pregnancy and abortion. The article concluded that the prevalence of premarital sex among Nigerian Christian youth is a challenge to the Church and postulated a sexual theology of the Church in which Deuteronomy 22:13-21 takes a central place. Taking a cue from the text, this theology would assign significant roles to the church community, the youth themselves and parents in a bid to provide sex education for the youth so that they avoid premarital sex. Intradisciplinary and/or interdisciplinary implications: This research involves the disciplines of the Old Testament and Christian ethics. It relates the narrative on virginity proof in Deuteronomy 22:13-21 to the Nigerian context with its high rate of premarital sex. The article postulates that the text can be employed in a sexual theology of the Church that would help in combating prevalent premarital sex.